Antilipase and antiproliferative activities of novel fluoroquinolones and triazolofluoroquinolones. (1st August 2017) - Arabiyat, Shereen; Kasabri, Violet; Al‐Hiari, Yusuf; Bustanji, Yasser K.; Albashiti, Rabab; Almasri, Ihab M.; Sabbah, Dima A.
Abstract : Fluoroquinolones (FQs) have been identified recently as potent inhibitors of pancreatic lipase (PL). The aim of this study was to synthesize novel FQs and triazolofluoroquinolones (TFQs) and to evaluate them in vitro with respect to their antilipolytic efficacy and potency properties. The PL‐IC50 values of 12 FQs and TFQs (3 (a–c )–6 (a–c )) were in the range of 12.5–189.1 μm . These values are further supported by docking studies. The suggested association between obesity and colorectal cancer initiated the evaluation of antiproliferative activity of the new FQs and TFQs against a panel of obesity‐related colorectal cells (HT29, HCT116, SW620 CACO2, and SW480). Sulforodamine B colorimetric assay revealed that some derivatives exhibited unselective cytotoxicity against HT29, HCT116, SW620 CACO2, and SW480. Remarkably, FQ4a 's selective cytotoxicity against HCT116 was found valuable with IC50 value of 4.2 μm which exceeds that of cisplatin with a substantial selective cytotoxicity in periodontal ligament fibroblasts. In conclusion, FQ and TFQ derivatives may unveil new antiobesity and anticancer agents in the future. Abstract : Novel FQs and TFQs are synthesized and evaluated in vitro with respect to their antilipolytic and antiproliferative efficacy and potency properties. The PL‐IC50 values of 12 FQs and TFQs (3 (a–c )–6 (a–c )) were in the range of 12.5–189.1 μm . FQ 4a's selective cytotoxicity against HCT116 was found valuable with IC50 value of 4.2 μm which exceeds that of cisplatin.